Empowering Education and Culture: A Guide to Employee Training and Skill Development Programs - Napat Panya Panya; Kanyawee Srisuk Srisuk; Thanakrit Phukhao Phukhao (Universal Education Jurnal Teaching and Learning, 2024)
This study explores the importance of strategic leadership in the development of educational institutions, with a particular focus on human resource development (HRD) in Thailand. HRD is recognized as a cornerstone for national progress, especially in the face of rapid technological changes and globalization. The paper emphasizes that HRD in the education sector must go beyond technical skills to include the development of moral values, ethics, and national character. The research utilizes a traditional literature review methodology to analyze existing sources related to HRD and employee training, offering actionable insights for the design and implementation of effective training programs. The findings underline the need for training initiatives that not only enhance technical competencies but also foster attitudes, behaviors, and interpersonal skills, ensuring that employees are equipped to handle the challenges of a rapidly changing global environment. This holistic approach to HRD is seen as crucial for the long-term sustainability of educational institutions and their ability to adapt to future demands. The study concludes by proposing guidelines for developing strategic leadership skills among school administrators to improve organizational effectiveness and contribute to societal development.